2009
DOI: 10.1111/j.1582-4934.2009.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural progenitors derived from human embryonic stem cells are targeted by allogeneic T and natural killer cells

Abstract: Neural progenitor cells (NPC) of foetal origin or derived from human embryonic stem cells (HESC) have the potential to differentiate into mature neurons after transplantation into the central nervous system, opening the possibility of cell therapy for neurodegenerative disorders. In most cases, the transplanted NPC are genetically unrelated to the recipient, leading to potential rejection of the transplanted cells. Very few data provide reliable information as to the potential immune response of allogeneic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
6

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 45 publications
3
58
0
6
Order By: Relevance
“…Similar to earlier reports on N hESCs and their differentiated progeny, we observed that PG NSCs expressed low levels of HLA-I proteins but no HLA-II or costimulatory molecules (16,18,19). HLA-I expression in PG NSCs was increased by IFN-γ treatment and reached PBMC levels as reported for N hESCs (16).…”
Section: R E S E a R C H A R T I C L Esupporting
confidence: 78%
See 2 more Smart Citations
“…Similar to earlier reports on N hESCs and their differentiated progeny, we observed that PG NSCs expressed low levels of HLA-I proteins but no HLA-II or costimulatory molecules (16,18,19). HLA-I expression in PG NSCs was increased by IFN-γ treatment and reached PBMC levels as reported for N hESCs (16).…”
Section: R E S E a R C H A R T I C L Esupporting
confidence: 78%
“…N NSCs induce proliferation of allogeneic T cells in a mixed lymphocyte reaction (MLR) despite the absence of costimulatory molecules (19,20). To address this property for PG NSCs, we recorded the response of healthy donor PMBCs to irradiated PG NSCs in allogeneic MLR reactions.…”
Section: Pg Nscs Are Less Immunogenic Than N Nscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the lack of MHC I on target cells, the activation of additional stimulatory NK receptors is necessary to trigger NK killing (Bryceson et al, 2006), and the expression of stimulating NK ligands can lead to lysis even in the presence of MHC I (Cerwenka et al, 2001). Murine ESCs have been shown to express high levels of the NKG2D ligands REA-1, H60, MULT-1 (Bonde and Zavazava, 2006;Dressel et al, 2008;Frenzel et al, 2009) and ICAM-1 (Frenzel et al, 2009), and blocking of these receptors prevents cell lysis (Frenzel et al, 2009;Preynat-Seauve et al, 2009). Murine ESC-derived cardiomyocytes, however, which are negative for MHC I but also negative for NKG2D ligands, were spared by NK cells (Frenzel et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Potential hESC-derived grafts would likely require no more immunosuppression than what is currently used for fetal neural grafts. It is worth mentioning, however, that 1 study [123] has shown that such a treatment may inhibit differentiation from PSC. This issue should be specifically considered before clinical implementation.…”
Section: Immunogenicity Of Striatal Neural Graftsmentioning
confidence: 99%